Color harmony logos : more than 1,000 colorways for logos that work - Simmons, Christopher, 1973-; Belonax, Tim.; Earhart, Kate. (Gloucester, Mass. : Rockport, 2006)
Accompanying CD-ROM contains ... "a selection of the featured logos. The CD lets users experiment with color and print the results for reference."--P. [4] of cover.
Keywords: Logos (Symbols); Color -- Psychological aspects; Color in design; Color in design -- Case studies